Elite-adapted wheelchair sports performance: a systematic review. Issue 2 (16th January 2017) - Perret, Claudio
Abstract: Purpose : Elite-adapted sports performance has considerably improved over the last decades and winning or losing races at Paralympic Games is often a matter of a split second. In other words, every single detail counts, which underlines the necessity of optimizing training interventions and equipment for athletes in order to achieve top-class performance. However, to date, studies which include Paralympic elite athletes are scarce. Methods : A comprehensive literature search was performed to identify potential strategies and interventions in order to optimize elite-adapted wheelchair sports performance, whereas the focus lay on respiratory muscle training (RMT), cooling (CI) and nutritional interventions (NI) as well as on individual equipment adaptations (IEA). Results : The total number of studies identified for the final analysis was six for RMT, two for CI, three for NI and seven for IEA, respectively. Results point predominantly towards performance enhancing benefits for CI and IEA, whereas NI and RMT provided inhomogenous findings. Conclusions : In comparison to the able-bodied population, research in the field of Paralympic elite sport is scarce. CI and IEA seem to have significant performance enhancing benefits, whereas NI and RMT revealed controversial findings. However, due to the limited number of elite athletes with a spinal cord injury available to participate in scientific studies, general conclusions are difficult to make at this stage and in daily practice recommendations are still given mainly on an individual basis or based on personal experiences of coaches, athletes and scientists. Implications for Rehabilitaton: Based on the knowledge gained in elite sports, wheelchair equipment could be optimized also for daily use. Elite sports performance could inspire wheelchair users to achieve their personal fitness goals.